2007
DOI: 10.1093/humrep/dem185
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory and inhibitory effects of genistein on human uterine leiomyoma cell proliferation are influenced by the concentration

Abstract: Genistein's effects are concentration-dependent in both cell lines. Lower concentrations elicit proliferative effects on UtLM cells only; whereas, higher concentrations alter morphology, inhibit proliferation, and increase caspase activity and apoptosis in both cell types, with the latter two effects being more extensive in UtSMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 48 publications
6
52
0
Order By: Relevance
“…The growth inhibition function of the two isoflavones on cancer cells vary with concentration, cell type and exposure time. For example, pure genistein and daidzein might exhibit biphasic effect on cancer cells, that is, the compounds showed inhibitory effect at high concentrations but displayed activating function at low concentrations [15][16][17]; or lower concentrations had more obvious apoptosis induction than higher concentrations [18]. It has also been reported that the two compounds alone inhibited certain malignant phenotype of melanoma via different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The growth inhibition function of the two isoflavones on cancer cells vary with concentration, cell type and exposure time. For example, pure genistein and daidzein might exhibit biphasic effect on cancer cells, that is, the compounds showed inhibitory effect at high concentrations but displayed activating function at low concentrations [15][16][17]; or lower concentrations had more obvious apoptosis induction than higher concentrations [18]. It has also been reported that the two compounds alone inhibited certain malignant phenotype of melanoma via different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Genistein is a small-molecule EGFR tyrosine kinase (TK) inhibitor, which can inhibit TK activation and subsequently lead to blockade of EGFR signaling pathway by competing with adenosine triphosphate (ATP) binding to the TK domain of the receptor, resulting in the suppression of cell proliferation and differentiation [12][13][14][15]. For this reason, EGFR inhibitors, such as genistein, always serve as agents for treating a variety of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of these tumors has been reported to be as high as 77% based on pathological specimens (3,4). Fibroids are noncancerous growths that develop in the muscular wall of the uterus, and they cause health problems such as pelvic pain, menorrhagia, and infertility (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of these tumors has been reported to be as high as 77% based on pathological specimens (3,4). Fibroids are noncancerous growths that develop in the muscular wall of the uterus, and they cause health problems such as pelvic pain, menorrhagia, and infertility (1,4). Etiology of fibroids is not well understood, although studies have shown that these tumors are hormonally dependent, similar to breast and ovarian cancers (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation